THE PHILOSOPHY OF SUFISM IN THE SCIENTIFIC RESEARCH OF UZBEK SCIENTISTS - Tursunkulova Shakhnoza Tuychiyevna (Western European Studies, 2023)
The article provides information about the scientific research of Uzbek scientists who have conducted scientific research on the teachings of Sufism and are currently conducting research. There are opinions about the unique characteristics, history, philosophy and methodology of Sufism.
Keywords: Sufism; sect; science; perfect man